Formation and Pathogenicity Variation of Oospores of Phytophthora capsici Infecting Black Pepper - DYAH MANOHARA (Microbiology Indonesia, 2007)
Phytophthora capsici Leonian is the causal agent of foot rot disease of black pepper (Piper nigrum L.). Foot rot disease is the most destructive disease which can cause significant economic losses of black pepper. Two mating types of P. capsici were found in black pepper plantations in Lampung. This research was aimed at examining the effects of temperature, light, and polycarbonate membrane on oospore formation. Also the effect of light on germination and determining both mating types of 30 randomly selected progenies. The results showed that oospores were produced through either hyphal contact or without any contact. Oospores were produced abundantly on V8 agar in the dark at 16-24 oC. Oospores germinated after 3-weeks incubation in the dark followed by 1-week incubation under TL fluorescent light. All progeny were heterothallic, and consisted of 16 isolates of A1 mating type and 14 isolates of A2 mating type. There was no correlation between mating type categories and their pathogenicities on black pepper leaves. Twenty-six progeny isolates may infect unwounded pepper leaves, whereas another four isolates may only infect wounded pepper leaves. Pathogenicities of all progenies were lower than those of their parents.